Hasil Belajar Matematika Siswa dengan Strategi Pembelajaran Ekspositori Menggunakan Media Interaktif Ispring Suite Kelas IX di MTsS Muhammadiyah Pakan Sinayan - Pratiwi, Wesi; Risnawita, Risnawita; Haida , Haida; Rahmat, Tasnim (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is backed by the observation results of the researcher, which show that the learning activities of ninth grade students are still teacher-centered. The teacher has used media in the form of teaching aids. However, it appears that the students are still not interested in the media provided. The purpose of this research is to determine whether the mathematics learning outcomes of students using the expository learning model with interactive media iSpring Suite in the ninth grade at MTs Muhammadiyah Pakan Sinayan. This study is an experimental research. The population in this study consists of all ninth grade students at MTsS Muhammadiyah Pakan Sinayan, which consists of 4 classes totaling 69 students. The sample was selected randomly (random sampling) after conducting normality tests, homogeneity of variance tests, and mean equality tests on the population. The sample size was 34 students. The research instrument used was a test to assess student learning outcomes. Based on the data analysis, the calculated t-value was greater than the critical t-value in both the control and experimental groups. Therefore, it was concluded that the mathematics learning outcomes of students using the expository learning strategy with interactive media iSpring Suite were better than those of students using the expository learning strategy without interactive media in Class IX at MTsS Muhammadiyah Pakan Sinayan.